Neutrophil to Lymphocyte Ratio Predicts Outcome of Stroke by Cervicocranial Arterial Dissection - Sun, Guangbi; Yang, Yi; Chen, Zhiguo; Yang, Le; Diao, Shanshan; Huang, Shicun; Wang, Yiqing; Wang, Yiting; Sun, Baoliang; Yuan, Xia; Xu, Xingshun (Frontiers in Medicine, 2020)
Background and Purpose: Neutrophil to lymphocyte ratio (NLR) is positively associated with poor prognosis in patients with cerebral infarction. The goal of this prospective study is to explore the predictive value of NLR in patients with acute ischemic stroke (AIS) caused by cervicocranial arterial dissection (CCAD). Methods: Ninety-nine patients with AIS caused by CCAD met criteria for inclusion and exclusion were selected for this study. We collected baseline data on the admission including NLR. The primary poor outcome was major disability (modified Rankin Scale score≥3) or death at 3 months after AIS. Results: A total of 20 (20.2%) patients had a poor outcome at 3 months after AIS. According to the 3-month outcome, the patients were divided into two groups and univariate and multivariable analyses were conducted. Among the risk factors, elevated NLR levels were independently associated with 3-month poor outcomes. Further, we made the ROC curve to evaluate the predictive value of NLR level on prognosis. The area under the curve was 0.79 and a cut-off value of NLR was 2.97 for differentiating the poor outcome. We divided patients into groups according to the cut-off value. Patients with high NLR have a higher risk of poor outcome than those with low NLR (P<0.05). Conclusion: As an inflammatory marker, elevated NLR levels were associated with 3-month poor outcome in AIS caused by CCAD.